Kerinduan Tokoh-tokoh Novel Rindu Kami Pada-Mu Karya Garin Nugroho dan Islah Gusmian: Analisis Semiotik - Sri Mariati (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
Novel Rindu Kami Pada-Mu reveals the lives of the peoples in the market and their life problems theyface. By using qualitative methods, it can be seen that the characters have a deep longing for lost loveand affection. The relationship between the sign and its reference in the form of icons, indices andsymbols, making the lives of those markets and the problems described Garin Nugroho and IslahGusmian be very interesting. The novel contains the suffering and struggle of the people in the marketto regain the lost affection. The novel implies that the poor and marginalized state or in a state rich andaffluent, people need attention and affection. In addition there is also a supporter of religious messagesconveyed discursive narrative and dramatic, both religious and social rituals of worship. Love oraffection is part of the value of one's religiosity, given that with love and affection, someone to worshipsocially.